Identification of a variant subgroup A strain of respiratory syncytial virus. - Mufson, M A (1996)
During epidemiologic surveillance of children with respiratory syncytial virus (RSV) disease in Huntington, W.Va., we identified seven strains of a new variant subgroup A RSV (subgroup A-Var) by their reactions in an enzyme immunoassay with two anti-F monoclonal antibodies (MAbs) specific for two epitopes, F1 and F4, generated against the subgroup B RSV. The prototype strain of subgroup A and all other subgroup A field strains from that epidemiologic year failed to react with these two subgroup B MAbs. Additional enzyme immunoassays with 18 subgroup B anti-F MAbs specific for 14 epitopes showed that subgroup A-Var strains also reacted with a MAb specific for the subgroup B F2 epitope. In a radioimmune precipitation assay, the molecular size of the subgroup A-Var F2 subunit of the fusion (F) protein clearly differed from those of both prototype strains of subgroup A and subgroup B RSV. The molecular size of the F2 subunit of subgroup A-Var (24 kDa) was intermediate between the size of the F2 subunit of subgroup A (25 kDa) and that of subgroup B (23 kDa). However, the molecular sizes of the F1 subunits of both subgroup A and subgroup A-Var were identical (54 kDa) and slightly larger than those of the F1 subunits of both subgroups B1 and B2 (53 kDa). These data suggest that subgroup A-Var may represent a distinct RSV A subgroup, analogous to subgroup B1 and B2 RSV, and it is the first-identified naturally occurring subgroup A RSV with an F protein different from that of the prototype A RSV.